CORRELATION BETWEEN RESULT OF ABDOMEN MDCT SCAN AND ERCP IN OBSTRUCTION ICTERIC PATIENT - Asnur, Ariany; Murtala, Bachtiar; Latief, Nikmatia; Seweng, Arifin; Daud, Nu’man As; Idris, Nurlaily (E-Jurnal Medika Udayana; Vol 10 No 3 (2021): Vol 10 No 03(2021): E-Jurnal Medika Udayana, 2021)
This study aims to find out correlation between result of abdominal MDCT scan abdomen and ERCP in obstruction icteric patient. This study was a cross sectional and retrospective study including all patient with intrahepatic or extrahepatic or both cholestatic in abdominal MDCT scan without and with contrass enhance and ERCP in Dr. Wahidin Sudirohusodo hospital, over period of two years and four months from January 2018 to Apriil 2020. Minimal 31 data were collected, using Kappa and p value <0,05. Among the 174 samples, 81 samples (46,6%) undergo abdominal MDCT scan without contrass enhance and 93% samples (53,4%) undergo abdominal MDCT scan with contrass enhance. Majority belong to 41-50 and 51-60 year age groups is 60 samples (34,5%) and 44 samples (25,35%). Males are more than females in number that is 57,5% dan 42,5%. there is correlation among result in abdominal MDCT scan without and with contrass enhance and ERCP in the cholestatic, location and cause of obstruction biliary. Majority cholestatic in intra and extrahepatic duct, the obstruction location in extrahepatic duct and the cause of obstruction is benign for MDCT scan without contrass enhance and malignant in MDCT scan with contrass enhance. There is significat correlation among cholestatic, location and cause of obstruction in abdominal MDCT scan without and with contrass enhance and ERCP.